Wrongness: Social Side-Effects in Psychotherapy. Issue 4 (18th May 2020) - Bugliani, Adriano
ABSTRACT: To help people own who they are, to get to their emotional basics, hold what they feel and be able to think even under the heaviest interpersonal pressure—this is my first and main therapeutic goal. The social consequences are that emotionally skillful people stop ignoring the inconsistencies they perceive in relationships; they ask for clarification once they no longer accept that their signaling is dismissed as "wrong" behavior. Their asking gives rise to fair conflicts, but a fair conflict is disrupting, because it involves a lot of bilateral exploration about established assumptions: relationships constantly exceed reached conclusions, if people have the courage to look at them with a fresh eye. This rupture-repair process is in turn based upon a degree of incongruence in human interactions as a source of endemic conflict: the mind is growing through its bridging of interactive gaps. Bearing the impact of full-range emotions arising from rupture-and-repair is anything but a comfortable societal ritual.